THE ROLE OF THE FORENSIC EXPERT DURING THE PRE-TRIAL INVESTIGATION - Lykhova, Sofiia; Romanenko, Roman (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose determination of the main issues when engaging an expert at the stage of pre-trial investigation, appointment of forensic examinations and organizational aspects that affect the quality of conducting examinations and expert studies appointed in criminal proceedings. Methods: the research was conducted using the methods of analysis, systematization, comparison and deduction. Results: forensic examination is one of the procedural sources of evidence, and the factual data taken from it are subject to investigation in the same way as the rest of the evidence obtained by other means. However, forensic examination is distinguished by its high scientific authority and, as a general rule, should exclude the subjectivity of evidentiary information obtained as a result of its conduct. Discussion: considered legal issues related to the appointment and conduct of forensic (judicial) examinations in criminal proceedings. Peculiarities of involvement of an expert at the stage of pre-trial investigation are studied. Ukraine, as a democratic state, recognizes health, honor and dignity of a person, his life, inviolability and security as the highest social value (Article 3 of the Constitution of Ukraine). Legal protection of a person against criminal encroachments on his life and health as the most important social values is provided by the state within the limits of national legislation thanks to the activities of law enforcement agencies. The investigator, inquirer, prosecutor shall immediately, but no later than 24 hours after submitting an application, notification of a committed criminal offense or after independently discovering from any source circumstances that may indicate the commission of a criminal offense, enter relevant information into the Unified Register of pre-trial investigations, start the investigation and, 24 hours after entering such information, provide the applicant with an extract from the Unified Register of Pre-trial Investigations. Involvement of a forensic expert in criminal proceedings is a procedural form of using special knowledge in judicial proceedings. According to Art. 242 of the Criminal Procedure Code of Ukraine, the examination is conducted by an expert at the request of a party to criminal proceedings or by order of an investigating judge or court, if special knowledge is required to clarify the circumstances relevant to criminal proceedings.